Enantioselective Synthesis of Functionalized Quaternary Stereocenters. Issue 27 (17th August 2015) - Manchoju, Amarender; Thorat, Rakesh G.; Pansare, Sunil V.
Abstract: An enantioselective synthesis of functionalized quaternary stereocenters was developed from amino alcohol derived (bromoalkylidene)morpholinones. Stereoselective cross‐coupling of the morpholinones with arylboronic acids or alkyl trifluoroborates provided a variety of disubstituted alkylidenemorpholinones. A highly stereoselective Prins reaction of the cross‐coupling products generated the target quaternary stereocenter. The Prins products are readily converted into a variety of acyclic, enantiomerically enriched, functionalized building blocks with a quaternary stereocenter. Abstract : A modular synthesis of functionalized quaternary stereocenters was developed. Key features of the methodology are the stereoselective synthesis of morpholinone‐based tetrasubstituted alkenes and diastereoselective Prins reactions of these alkenes. Removal of the amino alcohol portion of the morpholinone provides the target, quaternary stereocenter‐containing, building blocks.